Answer:
I really don't know but can u help with mine-_-
I'm sorry hun, i suck at math. If i knew how i would help you. Have you tried looking it up?
When you are multiplying an exponent directly into a number/variable with an exponent, you multiply the exponents together.
For example:
![(x^{2} )^{3} = x^6](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%20%29%5E%7B3%7D%20%3D%20x%5E6)
![(x^{3} )^5=x^{15}](https://tex.z-dn.net/?f=%28x%5E%7B3%7D%20%29%5E5%3Dx%5E%7B15%7D)
When you are multiplying a variable with an exponent by another variable with an exponent, you add the exponents together.
For example:
![(x^{2} )(x^{3})=x^{5}](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%20%29%28x%5E%7B3%7D%29%3Dx%5E%7B5%7D)
![(x^{1} )(x^{2})=x^{3}](https://tex.z-dn.net/?f=%28x%5E%7B1%7D%20%29%28x%5E%7B2%7D%29%3Dx%5E%7B3%7D)
![(\frac{(x^{-3})(y^{2})}{(x^{4})(y^{6})} )^{3}=\frac{(x^{-9})(y^{6})}{(x^{12})(y^{18})}](https://tex.z-dn.net/?f=%28%5Cfrac%7B%28x%5E%7B-3%7D%29%28y%5E%7B2%7D%29%7D%7B%28x%5E%7B4%7D%29%28y%5E%7B6%7D%29%7D%20%29%5E%7B3%7D%3D%5Cfrac%7B%28x%5E%7B-9%7D%29%28y%5E%7B6%7D%29%7D%7B%28x%5E%7B12%7D%29%28y%5E%7B18%7D%29%7D)
You multiply 3 into each exponent in the numerator and the denominator
![\frac{(x^{-9})(y^{6})}{(x^{12})(y^{18})}= \frac{y^{6}}{(x^{9})(x^{12})(y^{18})}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%5E%7B-9%7D%29%28y%5E%7B6%7D%29%7D%7B%28x%5E%7B12%7D%29%28y%5E%7B18%7D%29%7D%3D%20%5Cfrac%7By%5E%7B6%7D%7D%7B%28x%5E%7B9%7D%29%28x%5E%7B12%7D%29%28y%5E%7B18%7D%29%7D)
When you have a negative exponent, you move it to the other side of the fraction to make the exponent positive.
![\frac{y^{6}}{(x^{21})(y^{18})} = \frac{1}{(x^{21})(y^{12})}](https://tex.z-dn.net/?f=%5Cfrac%7By%5E%7B6%7D%7D%7B%28x%5E%7B21%7D%29%28y%5E%7B18%7D%29%7D%20%3D%20%5Cfrac%7B1%7D%7B%28x%5E%7B21%7D%29%28y%5E%7B12%7D%29%7D)
When you have something like this:
![\frac{x^{2}}{x^5}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%7D%7Bx%5E5%7D)
You subtract the exponents together, so:
![\frac{x^2}{x^5} = x^{2-5} = x^{-3} = \frac{1}{x^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2%7D%7Bx%5E5%7D%20%3D%20x%5E%7B2-5%7D%20%3D%20x%5E%7B-3%7D%20%3D%20%5Cfrac%7B1%7D%7Bx%5E3%7D)
Your answer is the second option
Answer:
x=9
Step-by-step explanation:
We can use similar triangles and ratios. Put the small triangle side over the large triangle side.
9cm 3x -20
---------- = ---------------- We need to add the sides to get to the larger triangle
72+9 cm 3x-20 + 56
We can cross multiply to solve
9 * (3x-20+56) = (72+9) * (3x-20)
Simplify
9*(3x+36) = 81*(3x-20)
Distribute
27x +324 = 243x -1620
Subtract 27x from each side
27x-27x +324 = 243x-27x -1620
324 = 216x-1620
Add 1620 to each side
324+1620 = 216x
1944 = 216x
Divide each side by 216
1944/216 = 216x/216
9=x
Answer:
(x + 5)(3x + 5)
Step-by-step explanation:
(x - 5)(x + 8) + (x + 5)(2x - 3) ← factor out (x + 5) from each term
= (x + 5)(x + 8 + 2x - 3)
= (x + 5)(3x + 5)